Hazards Analysis, within Departments and Occupations, for Hepatitis B Virus among Health Care Workers in Public Teaching Hospitals in Khartoum State; Sudan - Elmukashfi, Taha Ahmed (Glob J Health Sci, 2012)
BACKGROUND: Infection with hepatitis B virus (HBV) can lead to a range of clinical illnesses. OBJECTIVES: To examine hazards of hepatitis B virus associated with clinical departments and occupations; among health care workers in Public Teaching Hospitals in Khartoum State, Sudan. METHODS: The study was a cross sectional, facility-based study. It was conducted on stratified two-stage cluster random sample of 843 subjects of whom 324 were at high-hazard, 445 at moderate hazard, and 74 at low hazard; depending on degree of exposure to blood and body fluids of patients. To assess hazards of HBV among departments and occupations of HCWs, non-parametric methods of Chi-square test, was used. RESULTS: For Anti-HBc vulnerable departments was Renal Dialysis (100%); while for occupations was midwives (73.3%). For carrier rate (+ve HBsAg), highest rate found in department of Management (6.8%); while for occupations was Midwives (6.7%). Regarding immunity (+ve Anti-HBs), the highest percentage found in the department of Dentistry (25.9%); while for occupations was associated with Doctors (14.8%). For a profile of high infectivity (+ve HBeAg), the most vulnerable department in terms of HBV hazards was the Surgery (1.4%); while for occupations was nurses (0.9%). CONCLUSION: There was a significant association for infection rate of HBV with occupation and type of department. The most hazardous departments, was Surgery with a profile of high infectivity rate, followed by other departments (medicine, pediatrics, psychiatry & ophthalmology). As for occupations, the most hazardous group was nurses group with a profile of high infectivity rate